The impact of housing assistance on the employment outcomes of labour market programme participants in Australia - Feeny, S.; Ong, Rachel; Spong, H.; Wood, G. (Carfax Publishing and Taylor and Francis Ltd for the University of Glasgow, 2011)
This paper examines whether the employment outcomes of Australian labour market programme participants vary according to whether they receive housing assistance. This issue attracted attention when a series of US studies showed that clients of welfare-to-work programmes are more likely to achieve positive employment outcomes if housing assistance is also received. This paper tracks the employment outcomes of labour market programme participants utilising six waves of data from the Household Income and Labour Dynamics in Australia (HILDA) database. Findings from a random effects model suggest that housing assistance status has little impact (either negative or positive) on employment outcomes. Differences in the institutional arrangements governing access to housing assistance could be responsible for the absence of any effect in Australia.